Comparison on antioxidant activity of fresh and oven dried extracted mixture of five different types of traditional herbs (Psidiumguavajava, Fern, Cymbopogonn, Pandanus Amaryfollius and Betel): article - Adniruddin, Amirah; Ibrahim, Ummi Kalthum (2017)
This study aimed to assess the effect of solvent concentration and temperature during extraction on chemical composition and antioxidant activity of fresh mixture and dried mixture of Psidiumguavajava, Fern, Cymbopogonn, Pandanus amaryfollius and Betel using DPPH radical scavenging analysis and gas chromatography-mass spectrometry (GC-MS) analysis. The herbs were divided into two which are fresh sample and oven dried sample. The sample were then extracted using different concentration of methanol (0,30,50,70 %) in a shaking water bath at temperature 60°C and 90°C for 30 min at 100 rpm. The antioxidant activities were dependent on the solvent concentration used and the temperature during extraction. The condition of the sample whether dried or fresh also shows different antioxidative activities. The optimum conditions for extraction of antioxidant from the herb mixture appeared with methanol composition of about 30% at 60 °C for 30 min with oven dried sample followed by distilled water extraction at 60°C with oven dried samples. The antioxidant activity in oven dried samples was higher than that in the fresh samples due to the high moisture content of the fresh sample. The GC-MS analysis characterized Octen-1-ol,3,7-dimethyl (0.240%), cis-á Terpineol (0.334%) and 6-Octenal, 3,7-dimethyl (0.205%) as a major component in the extracts.